TRANSIDIOMA - Jacquemet, Marco (Revista da Anpoll, 2016)
In this paper I will sketch the evolution of the concept of transidiomatic practices from my first analysis of the “transidiomatic floater” as an example of these practices (JACQUEMET 2005) to the current all-encompassing concept of the “transidioma” (JACQUEMET forthcoming). This work is licensed under a Creative Commons Attribution 3.0 License.